Superabsorbent hydrogels based on polysaccharides for application in agriculture as soil conditioner and nutrient carrier: A review - Guilherme, Marcos R.; Aouada, Fauze A. [UNESP]; Fajardo, André R.; Martins, Alessandro F.; Paulino, Alexandre T.; Davi, Magali F.T.; Rubira, Adley F.; Muniz, Edvani C. (Elsevier, 2015)
Superabsorbent hydrogels (SH) continue being a very important issue in both academic and industrial fields due to their applications in several technologies. This is proved by the impressive number of publications, through papers and patents as well, dealing with SH. This review is targeted to update and discuss some important aspects of synthesis, characterization and application of SH in agriculture, mainly those based on polysaccharides, as soil conditioners and as polymer carriers for nutrient release. Basic properties of SH and some methods for chemically modifying polysaccharides are given and some directions for hydrogels preparation are highlighted as well. Mechanisms associated with water transport into the 3D matrix, taking into account the transference of mass from hydrogel-soil system to plant, are discussed in the light of some mathematical models. Release of nutrients either from granules coated by hydrophilic polymer or from SH, targeting applications in agriculture, is also discussed on the basis of often used mathematical models (the swelling-based kinetic models) and on a diffusion-based kinetic model with a partition activity coefficient. Examples of recent applications in agriculture as soil conditioners and carriers for nutrient release (fertilizers, etc.) are given. At the final, future trends and perspectives are considered. More than two hundreds references are cited in the whole text.
Keywords: Plant-nutrient carriers; Polysaccharide-based hydrogels; Soil conditioners; Superabsorbent hydrogels; Superabsorbent hydrogels applied to agriculture